(1213) Branch-and-bound revisited: a survey of basic concepts and their applications in scheduling إعادة النظر في مفهوم التفرع والتقييد: دراسة استقصائية للمفاهيم الأساسية وتطبيقاتها في الجدولة - Elmaghraby, Salah E; Elshafei, Alwalid N. (The Institute Of National Planning., 2018)
The term "branch-and-bound" (B&B) has increasingly become a household term among students and researchers in the field of scheduling and sequencing.in this chapter we shall take a fresh look at this approach and assess its content, utility and potential.